The Impact of the COVID-19 Pandemic on Depression and Sexual Function: Are Pregnant Women Affected More Adversely? - Ramazan Denizli; Önder Sakin; Kazibe Koyuncu; Nayif Çiçekli; Nihat Farisoğulları; Mikail Özdemir (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To investigate depression and sexual function among pregnant and nonpregnant women throughout the COVID-19 pandemic. Methods A total of 188 women, 96 pregnant and 92 non-pregnant were included. The Beck Depression Inventory (BDI) and the Arizona Sexual Experience Scale (ASEX) were applied to the participants after obtaining sociodemographic data. Results The depression scores of pregnant and non-pregnant women were similar (p = 0.846). We found that the depression scores were significantly higher among the group of participants who have lower economic status (p = 0.046). Moreover, the depression score was significantly higher among women who lost their income during the pandemic (p = 0.027). The score on the ASEX was significantly higher, and sexual dysfunction was more prevalent among women who have lower levels of schooling and income (p < 0.05). Likewise, the ASEX scores were significantly higher (p = 0.019) among the group who experienced greater income loss throughout the pandemic. Upon comparing the pregnant and non-pregnant groups, we detected that sexual dysfunction had a significantly higher rate among pregnant women (p < 0.001). Conclusion In times of global crisis, such as the current pandemic, low-income families have an increased risk of experiencing depression and sexual dysfunction. When we compared pregnant women with non-pregnant women, depression scores were similar, but pregnant women were at a 6.2 times higher risk of developing sexual dysfunction.